Signs and Symptoms in the Temporomandibular Joint of Geriatric Patients with Arthritis, Before and After Physiotherapy - Mendiburu DDS, MSc, PhD, Celia (2016)
The temporomandibular joint (TMJ) may be affected in patients with rheumatoid arthritis and osteoarthritis, especially in elderly and senile adult patients. The objective of this study was to evaluate the signs and / or symptoms of TMJ in elderly subjects retired from a medical institution in Merida, Yucatan, Mexico, previously diagnosed with arthritis, the onset of physical therapy and one month after applying it. July-August 2015. A longitudinal, comparative and analytical study was conducted in 25 subjects ages 60 and older,   both sex: men and women. The subjects who agreed to participated signed voluntary consent letter. Also, a medical research card was made, which consisted of: 1) demographic and medical data; 2) a directed interview based on Rodriguez-Osores and modified by Mendiburu-Zavala in 2015 that included 33 dichotomous questions related to signs and / or symptoms of TMJ disorders; 3) the clinical examination was carried out carefully; 4) Finally, a manual prepared by Mendiburu-Zavala exercise based on Rocabado-Seaton and  Lawson´s manual.  The exercises for relaxation of the jaw and face, posture and managing TMJ noises were taught and explained individually, offering to teach them the times they needed to exercise at home. The questionnaire and clinical examination was applied a month later. The McNemar test was used. It was considered significant if P <0.05.  A 28 % of the studied subject were men and 72 % women, with an average age of 65.4 ± 4.8, with a 44 % with osteoarthritis and a 56 % with rheumatoid arthritis.  The effect of physiotherapy per month being applied, had a significantly favorable responses of " NO" for variables : blocked, jammed or dislocated jaw (P = 0.0156); Crackles ( P = 0.0195 ) and Snap ( P = 0.0001 ). The application of physiotherapy in this age group with arthritis was favorable.